Airway clearance technique therapy for atelectasis induced by scoliosis surgery: a case report - Rui Zhai; Hairong Su; Yaxu Wu; Rong Tan; Xiaoli Zhang; Ye Tian; Mei Hu (Frontiers in Medicine)
The patient, a 55-year-old female presenting with spinal deformity and exertional dyspnea, was referred to the hospital. Radiographic evaluation of her spine revealed an “S”-shaped scoliosis with a Cobb angle measuring 68°, indicative of severe scoliosis. Despite receiving medication for expectoration, postoperative symptoms including chest tightness, breathlessness, and ineffective coughing persisted and progressively worsened. Subsequent chest CT scans demonstrated extensive atelectasis, and pharmacological interventions proved to be ineffective. Considering the patient’s clinical condition, we implemented airway clearance technique (ACT) along with prone ventilation to optimize cough effectiveness and mitigate atelectasis formation. The airway clearance techniques (ACT) employed include nebulization, continuous positive expiratory pressure (CPEP), and continuous high frequency oscillation (CHFO). Chest CT imaging confirmed that ACT substantially alleviated the patient’s pulmonary atelectasis. Moreover, blood gas analysis indicated significant improvements in both the PaO2/FiO2 ratio and base excess of whole blood. Follow-up evaluation 1 year post-discharge revealed a favorable prognosis for the patient. We anticipate that our experience utilizing these novel therapeutic modalities will provide valuable insights for clinicians managing similar complications.